STUDI FENOMENOLOGI TENTANG MAKNA HIDUP PADA PEREMPUAN PELAKU ABORTUS PROVOCATUS CRIMINALIS DALAM FASE REMAJA DI KOTA SURABAYA - Sri Dewi Indah Lestari; Agustina Engry (EXPERIENTIA : Jurnal Psikologi Indonesia, 2019)
Teenagers as perpetrators of abortion provocatus criminalis have both physical and psychological effects, because decisions taken to undergo abortion is very dilemma, controversial, and risky. In fact, often women who carry out abortion provocatus criminalist they feel embarrassed, afraid, sad, stresssed, feel guilty, want to commit suicide and so on. Therefore, it is very possible the psychological condition of a teenager who has performs abortion provocatus criminalist, is dynamic in terms of movement from the psychological condition of pre-abortion, when to execute an abortion, and post-abortion. The movement of these psychological conditions raises the concept of meaningful life that comes from creative values, experiential values, and attitudinal values. This study uses qualitative methods with phenomenology models. The technique used was an interview with an inductive model coding and categorization analysis, which involved two informants who acted as perpetrators of criminalist provocatus abortion in their teenagers. The validity of the research conducted was communicative validity and argumentative validity. This study found that the meaning of life of women perpetrators of abusive provocatus criminalis at the age of adolescence originated from creative values, experiental values and attitudional values. These values give rise to an expectation for individuals who are used as guidelines in carrying out their daily lives. On the other, also raises risk factors such as the invitation from friends to return to the world of free association made the informants dynamically, even though her self promised not to return to the bad world. Whereas factors protective such as commitment, new family and reflection on past experiences provide reinforcement to defend expectations that act as life goals.